MALAY THOUGHT ON MANNERS AND KNOWLEDGE: EXPLORING MORAL VALUES AND NATURE IN PANTUN - Mohamad Judi, Hairulliza; Nik Khalili, Nik Suhaila Yasmina; Amirham, Ifwat Amzar (Jurnal 'Ulwan, 2023)
Pantun acts as a symbol in communication among Malay community whose values and rhyme are inseparable from the culture and heritage of the ancestors. Pantun contains local wisdom in the form of advice, morality, and appreciation of nature and its surroundings. The values in pantun correlate with Islamic teachings making the poetry continue to be relevant, particularly to observe the best manners while interacting with others, and to be keen in searching for and adopting knowledge. As expected, pantun that offers sound advice listed amongst the most timeless, including for the younger generation. In contemporary Malaysia, tech-savvy generation interact with pantun in various social media platforms such as Facebook, and Instagram and a range of computing techniques like augmented reality and mobile game. In long term, this project aims to design and develop mobile game application to facilitate children in learning pantun and explore nature and wisdom being hidden behind the words. Unfortunately, limited research examines both components to serve as the basis for the game learning content. Thus, this paper aims to discuss elements of morality and nature in Pantun using flora and fauna components. These two components appear to be dominant in pantun to mould the identity of Malays. The findings show that pantun demonstrates great respect for nature and applies aesthetic language to teach wisdom. To offer advice, pantun presents the message only after providing appreciation to nature. The intrinsic interpretations of pantun reveal that they are full of elements related to manners and knowledge. To name a few, good ethics, politeness, education, and teachings are all consistent with the Islamic teaching on universal guidance to mankind.